Trang chủ » Hỏi đáp » Môn Toán a. (x-2)($x^{2}$+2x+4)-(x-1)$^{3}$+7 ‘ b. x(x-2)(x+2)+(x+3)($x^{2}$-3x+9) 30/04/2024 a. (x-2)($x^{2}$+2x+4)-(x-1)$^{3}$+7 ‘ b. x(x-2)(x+2)+(x+3)($x^{2}$-3x+9)
Giải đáp: a)3x^2-3x b)2x^3-4x+27 Lời giải và giải thích chi tiết: a) (x-2)(x^2+2x+4)-(x-1)^3+7 =x^3-2^3-(x^3-3x^2+3x-1)+7 =x^3-8-x^3+3x^2-3x+1+7 =(x^3-x^3)+3x^2-3x+(-8+1+7) =3x^2-3x b) x(x-2)(x+2)+(x+3)(x^2-3x+9) =x(x^2-4)+(x^3+3^3) =x^3-4x+x^3+27 =2x^3-4x+27 Trả lời
1 bình luận về “a. (x-2)($x^{2}$+2x+4)-(x-1)$^{3}$+7 ‘ b. x(x-2)(x+2)+(x+3)($x^{2}$-3x+9)”